Stacking fault tetrahedra in metals. (1st January 2015) - Loretto, M.H.; Phillips, P.J.; Mills, M.J.
Abstract: Mechanisms for the formation of stacking fault tetrahedra in metals are critically reviewed in the light of recent observations, where it is claimed, incorrectly, that for the first time stacking fault tetrahedra have been observed, which are formed by a dislocation mechanism, without the involvement of vacancies. In this note the experimental conditions where stacking fault tetrahedra have been observed are defined, together with the mechanisms that have been put forward to explain the observations. Three fundamentally different mechanisms are identified.